Preseason Body Composition Is Associated With In-season Player Availability in Elite Male Australian Footballers. Issue 5 (17th May 2023) - McCaskie, Callum J.; Sim, Marc; Newton, Robert U.; Heasman, Jarryd; Rogalski, Brent; Hart, Nicolas H.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: McCaskie, CJ, Sim, M, Newton, RU, Heasman, J, Rogalski, B, and Hart, NH. Preseason body composition is associated with in-season player availability in elite male Australian footballers. J Strength Cond Res 37(5): 1089–1095, 2023—The purpose of this study was to examine whether end of preseason body composition characteristics was associated with in-season match availability and injury. Sixty ( n = 60) elite Australian football players had body composition characteristics assessed using dual-energy X-ray absorptiometry across 3 seasons (2016, 2018, and 2021). Match availability and injury were recorded throughout each season. Pearson's correlations were calculated to assess the associations between body composition and in-season match availability and injury. Logistic regression models were used to assess the odds of missing games as a result of injury throughout a season. Regional lean soft tissue mass asymmetry and its relationship to injury and availability was explored. Statistical significance was set at p ≤ 0.05. Body composition characteristics expressed as relative values seemed to be more highly associated with in-season availability and injury than characteristics expressed as absolute values. Players with lower relative fat mass (FM) (<12.1% total body FM) were available for 89.7% of in-season matches compared with 80.7% for players with higher relative FM (>12.1% total body FM). Subsequently, players with higher relative FM had 3.3–3.5 times greater odds of missing one game to injury (odds ratio [OR] = 3.33; 95% confidence interval [CI] = 1.00–11.14; p ≤ 0.05) and missing 2 or more games to injury (OR = 3.50; 95% CI = 1.20–10.20; p ≤ 0.05) throughout a season compared with players with lower relative FM. Higher proportions of fat mass may accelerate the onset of fatigue and place players at a greater risk of injury. Reducing players' FM across the preseason phase should be a key aim for practitioners to reduce the odds of injury throughout the competitive season.